Physical and Thermal Properties of Potato Flour as Influenced by Moisture Content - Raigar, Rakesh Kumar; Mishra, Hari Niwas (Journal of Agricultural Engineering, 2018)
The physical, thermal and flow properties (flowability) of potato flour from Kufri-Chipsona, Kufri Sinduri and Kufri Badshah varieties produced in West Bengal, Rajasthan and Bihar states were evaluated. Moisture content was the important variable affecting these properties. Within moisture ranges of 7.04 % to 56.25 % (d.b.) the bulk, tapped and true density and porosity significantly decreased with increase in moisture content of potato flour of each variety, and ranged from 350-690 kg.m-3, 640-1240 kg.m-3, 1510-1550 kg.m-3 and 54-71 %, respectively. Carr index and Hausner ratio ranged from 24.41-44.50 %, and 1.32-1.77, respectively. Thermal conductivity, specific heat and thermal diffusivity of the flours significantly (p<0.05) increased from 0.125 to 0.230 W.mâˆ’1.K-1, 0.092 to 0.124 mm2.s-1 and 1.13 to1.76 MJ.m-3.K-1, respectively, when moisture content of flours increased from 7.04 % to 56.25 % (d.b.).